Revised energy levels and hyperfine structure constants of Ta II. (June 2016) - Windholz, Laurentius; Arcimowicz, Bronislaw; Uddin, Zaheer
Abstract: Using a wave number calibrated Fourier transform spectrum, we determined the energy levels of the first ion of tantalum with high accuracy. To get the correct center of gravity wave numbers of the observed spectral lines, the knowledge of the hyperfine constants of the involved levels was necessary. From the observed values we deduced the energy levels in a global fit. A comparison between our results and all available literature values is presented. Highlights: Newly determined level energies of Ta II with accuracy better than 0.01 cm −1 . Reliable hyperfine structure constants for nearly all Ta II energy levels. Compilation of data on energy and hyperfine structure of Ta II.